Deletion variant rs35153737 in TOR1A is associated with isolated dystonia in a Southwestern Chinese Population. (14th September 2017) - Li, Jiang; Long, Yuzhou; Huang, Xiaoqin; Chen, Yuan; Chen, Weikang; Liu, Shang; Chu, Jiayou; Yang, Zhaoqing; Sun, Hao; Fang, Kewei
Highlights: Our study found mutation in the 3′-UTR of TOR1A : NM_000113.2:c.*414delG (rs35153737). This study suggested that there is an association between rs35153737 and dystonia in a southwestern Chinese population. Abstract: Background: TOR1A plays a very important role in early-onset isolated dystonia. Studying the association between the common variants of this gene and dystonia can help us understand the connection between TOR1A mutations and this disease. Methods: The TOR1A exon 5 was sequenced in 223 isolated dystonia patients and 210 age-adjusted controls. Patients and controls all came from Southwest China. Results: The following two common variants were found in the 3′-UTR of TOR1A : NM_000113.2:c.*414delG (rs35153737) and NM_000113.2:c.*824delG (rs3842225). The rs35153737 variant showed a statistically significant association with dystonia using the allele model ( P  = 0.035) and the dominant genetic model ( P  = 0.018); however, no association between rs3842225 and dystonia was found. Conclusion: Our study suggests that there is an association between rs35153737 and dystonia in a southwestern Chinese population, and it may be caused by high linkage disequilibrium between this deletion and potential pathogenic variants in TOR1A .